2005
DOI: 10.1093/eurheartj/ehi293
|View full text |Cite
|
Sign up to set email alerts
|

Early eptifibatide improves TIMI 3 patency before primary percutaneous coronary intervention for acute ST elevation myocardial infarction: results of the randomized integrilin in acute myocardial infarction (INTAMI) pilot trial

Abstract: In this pilot trial, double bolus eptifibatide given in the emergency room improved TIMI 3 grade flow of the infarct-related coronary artery before PCI. These results should be confirmed in a larger trial and whether this advantage translates into an improvement in clinical outcome should be tested in a trial with primary clinical endpoints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 40 publications
2
40
1
1
Order By: Relevance
“…Previous studies have shown that the application of platelet glycoprotein IIb/IIIa receptor antagonists before primary PCI obviously improves the prognosis of patients (Cutlip et al, 2003;Lee et al, 2003;Zeymer et al, 2005;Emre et al, 2006;Gabriel et al, 2006;Gibson et al, 2006;Rakowski et al, 2007;De Luca et al, 2008). This finding is consistent with the results of our research.…”
Section: Disscussionsupporting
confidence: 93%
“…Previous studies have shown that the application of platelet glycoprotein IIb/IIIa receptor antagonists before primary PCI obviously improves the prognosis of patients (Cutlip et al, 2003;Lee et al, 2003;Zeymer et al, 2005;Emre et al, 2006;Gabriel et al, 2006;Gibson et al, 2006;Rakowski et al, 2007;De Luca et al, 2008). This finding is consistent with the results of our research.…”
Section: Disscussionsupporting
confidence: 93%
“…This result was supported by many studies which consistently reported better outcomes with upstream or early use of glycoprotein IIb/IIIa inhibitor compared with deferred treatment or other strategies (LOE 1 [452][453][454][455][456][457][458][459][460][461][462][463][464][465][466][467] ; LOE 2 468 -473 ; LOE 3 474 ; LOE 4 [475][476][477][478] ; LOE 5 479 ).…”
Section: Consensus On Sciencementioning
confidence: 75%
“…If a delayed primary PCI is expected, platelet glycoprotein IIb/IIIa receptor antagonists or low dose thrombolytic drugs in the early phase of AMI should be administered to restore early IRA patency and increase the chances of achieving a post-procedural TIMI 3 fl ow. [13] Lee et al [14] reported that a systolic BP (SBP) <120 mmHg in patients with AMI was associated with a higher mortality than in those with SBP >120 mmHg. A previous study showed that a low SBP <120 mmHg decreased coronary blood flow (CBF), collateral blood fl ow, and increased infact size.…”
Section: Discussionmentioning
confidence: 99%